Mitochondrial DNA is a direct target of anti-cancer anthracycline drugs. - Ashley, N; Poulton, J (2009)
The anthracyclines, such as doxorubicin (DXR), are potent anti-cancer drugs but they are limited by their clinical toxicity. The mechanisms involved remain poorly understood partly because of the difficulty in determining sub-cellular drug localisation. Using a novel method utilising the fluorescent DNA dye PicoGreen, we found that anthracyclines intercalated not only into nuclear DNA but also mitochondrial DNA (mtDNA). Intercalation of mtDNA by anthracyclines may thus contribute to the marked mitochondrial toxicity associated with these drugs. By contrast, ethidium bromide intercalated exclusively into mtDNA, without interacting with nuclear DNA, thereby explaining why mtDNA is the main target for ethidium. By exploiting PicoGreen quenching we also developed a novel assay for quantification of mtDNA levels by flow-cytometry, an approach which should be useful for studies of mitochondrial dysfunction. In summary our PicoGreen assay should be useful to study drug/DNA interactions within live cells, and facilitate therapeutic drug monitoring and kinetic studies in cancer patients.